Dot immunoperoxidase assay using monoclonal antibody for direct detection of cytomegalovirus in urine samples. - Zerbini, M (1987)
A rapid, simple dot immunoperoxidase assay for the direct detection of cytomegalovirus in clinical urine samples was developed. The assay was performed on nitrocellulose paper dotted with urine pellets free of cellular debris. Cytomegalovirus was detected with a monoclonal antibody to the capsid antigen, and the complex was visualized by immunoperoxidase staining. Positive reactions appeared as well-defined dark blue spots. Of the 87 urine samples examined, 10 proved positive in the dot immunoperoxidase assay, and 77 proved negative. The results agreed completely with the detection of cytomegalovirus-induced antigens in cell cultures inoculated with clinical specimens.